PRICAI 2018. trends in artificial intelligence : 15th Pacific Rim International Conference on Artificial Intelligence, Nanjing, China, August 28-31, 2018, Proceedings /: trends in artificial intelligence : 15th Pacific Rim International Conference on Artificial Intelligence, Nanjing, China, August 28-31, 2018, Proceedings. Part I : (2018) - Unknown
No abstract available